Optimization of Biocatalytic Production of Enantiopure (S)-1-(4-Methoxyphenyl) Ethanol with Lactobacillus senmaizuke Using the Box-Behnken Design-Based Model - Kavi, Mervenur; Ozdemir, Akin; Dertli, Enes; Sahin, Engin (SPRINGER HEIDELBERG, 2022)
Enantiomerically pure (S)-1-(4-methoxyphenyl) ethanol is a significant molecule for the production of various drug intermediates. (S)-1-(4-methoxyphenyl) ethanol was synthesized from 4-methoxyacetophenone using Lactobacillus senmaizuke as a biocatalyst. In addition, optimization of experimental conditions is important to analyze the role of culture parameters for catalytic bioreduction reactions. For this particular purpose, the experimental conditions of pH, incubation period, temperature, and agitation speed were investigated with the Box-Behnken experimental design-based proposed optimization model. (S)-1-(4-methoxyphenyl) ethanol, which can be used for the synthesis of antihistamines, including diphenhydramine hydrochloride and loratadine cycloalkyl [b] indoles that have the treatment function for an allergic response, was obtained in > 99% conversion, > 99% enantiomeric excess and 96% yield with whole cells of L. senmaizukei at this optimization conditions: pH = 5.80, the temperature = 29 degrees C, incubation period = 50 h, and agitation speed = 155 rpm. The bioreduction of 4-methoxyacetophenone efficiency was importantly affected by the quadratic and linear effects of experimental design parameters. Besides, the results demonstrate the importance of design parameters for catalytic bioreduction reactions. It is also concluded that the results show the effectiveness of the Box-Behnken experimental design-based proposed model to obtain optimum operating conditions of design parameters for catalytic bioreduction reactions.
Keywords: Box-Behnken design; Optimization; Asymmetric bioreduction; Biocatalysts; (S)-1-(4-Methoxyphenyl) ethanol; ASYMMETRIC REDUCTION; KINETIC RESOLUTION; LIPASE; CELLS; STRATEGIES; ALCOHOLS; LIGANDS; IMPROVE; KETONES; ACIDS; Science & Technology - Other Topics